آثار انضمام العراق إلى منظمة التجارة العالمية على القطاع الزراعي (المجلة العراقية للعلوم الاقتصادية, 2018)
The current study aims tostudy and analysis the potential effects of Iraq joining to the world trade organization on the agricultural sector. Iraq has been seeking to join this organization since 2004. The researeser used the descriptive and statistical analysis employing some agricultural sector indicators in Iraq and it was clear that the performance of the agricultural sector is poor and that it is (the agricultural sector) to meet the local needs and as well as being characterized by the chronic deficit in the commercial balance of the agricultural products. The researcher reached to several conclusions as the following: if Iraq joins to the international trade organization, that will reflect negatively on the agricultural sector, rise in the prices of most of the imported agricultural products, incapability of the locally-produced products to access to the external markets, the fierce competition of the foreign agricultural products with the local agricultural products and that needs the rehabilitation and developing the agricultural sector before joining the international trade organization.